Upaya Guru Pendidikan Agama Islam dalam Membentuk Akhlakul Karimah Siswa Kelas III SDN 1 Gadingan Kec. Sliyeg Kab. Indramayu - Ricoh Herlambang; Suci Muzfirah (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2026)
This study aims to determine the character of third-grade students and the efforts of Islamic Religious Education teachers to improve their character at SDN I Gadingan, Sliyeg District, Indramayu Regency. The background of this study is based on the importance of education in shaping the personality and morals of students, particularly through Islamic Religious Education learning. This study used a descriptive qualitative approach. Data collection techniques included observation and interviews. The primary data source in this study was the Islamic Religious Education teacher, Mr. Muhidin. The results showed that the character of third-grade students' character was still not fully aligned with the values ​​taught. This was evident in students' dress behavior, such as students still wearing clothing that did not comply with school regulations, and in their communication styles, where some students still showed little respect for their elders. Efforts made by Islamic Religious Education teachers to improve students' character include providing ongoing reprimands and advice, as well as providing role models in daily attitudes and behaviors within the school environment. These efforts are considered quite effective in forming and improving students' noble character.